An Endogenous Retroviral LTR-Derived Long Noncoding RNA lnc-LTR5B Interacts With BiP to Modulate ALV-J Replication in Chicken Cells - Chen, Shihao; Zhao, Ruihan; Wu, Ting; Wang, Dedong; Wang, Biao; Pan, Shiyu; Hu, Xuming; Pan, Zhiming; Cui, Hengmi (Frontiers in Microbiology, 2021)
Infection with the avian leukosis virus subgroup J (ALV-J) impairs host genes and facilitates the establishment of chronic infection and the viral life cycle. However, the involvement of long noncoding RNAs (lncRNAs) in ALV-J infection remains largely unknown. In this study, we identified a novel chicken lncRNA derived from LTR5B of the ERV-L family (namely lnc-LTR5B), which is significantly downregulated in ALV-J infected cells. lnc-LTR5B was localized in the cytoplasm and was relatively high expressed in the chicken lung and liver. Notably, the replication of ALV-J was inhibited by the overexpression of lnc-LTR5B but enhanced when lnc-LTR5B expression was knocked down. We further confirmed that lnc-LTR5B could bind to the binding-immunoglobulin protein (BiP), a master regulator of endoplasmic reticulum (ER) function. Mechanistically, lnc-LTR5B serves as a competing endogenous RNA for BiP, restricting its physical availability; Upon ALV-J infection, the reduction of lnc-LTR5B released BiP, which facilitated its translocation to the cell surface. This is crucial for ALV-J entry as well as pro-survival signaling. In conclusion, we identified an endogenous retroviral LTR-activated lnc-LTR5B that is involved in regulating the cell surface translocation of BiP, and such regulatory machinery can be exploited by ALV-J to complete its life cycle and propagate.